2007
DOI: 10.1089/neu.2006.0211
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Modal Magnetic Resonance Imaging Alterations in Two Rat Models of Mild Neurotrauma

Abstract: Magnetic resonance imaging (MRI) is increasingly used in the assessment of the severity and progression of neurotrauma. We evaluated temporal and regional changes after mild fluid percussion (FPI) and controlled cortical impact (CCI) injury using T2-weighted-imaging (T2WI) and diffusion-weighted imaging (DWI) MRI over 7 days. Region of interest analysis of brain areas distant to the injury site (such as the hippocampus, retrosplenial and piriform cortices, and the thalamus) was undertaken. In the hippocampus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 34 publications
5
55
0
1
Order By: Relevance
“…58 Although a recent study presenting bidirectional changes in FA of mTBI patients raised the possibility of spatial factors contributing to alterations in FA, 59 our data support rather the significance of temporal factors: both FA and MD changed significantly in a relatively short period, and no bidirectional changes were detected. The rapid consolidation of MD hypothetically may be associated with the recovery process from edema, because edema is thought to pass over in a similar pace after mTBI.…”
Section: Diffusion Tensor Imagingsupporting
confidence: 46%
“…58 Although a recent study presenting bidirectional changes in FA of mTBI patients raised the possibility of spatial factors contributing to alterations in FA, 59 our data support rather the significance of temporal factors: both FA and MD changed significantly in a relatively short period, and no bidirectional changes were detected. The rapid consolidation of MD hypothetically may be associated with the recovery process from edema, because edema is thought to pass over in a similar pace after mTBI.…”
Section: Diffusion Tensor Imagingsupporting
confidence: 46%
“…Although myelin only accounts for approximately 13% of total water in white matter compartments, a reduction in this percentage would theoretically also decrease diffusivity perpendicular to the axon. 30 At a more basic level, there may be qualitative differences in neuropathologic processes among appropriately diagnosed mTBI patients as illustrated by a recent study 34 comparing the fluid percussion (FPI) and cortical impact (CCI) injury models. Injured animals from both groups differed from shams in terms of T2 values and apparent diffusion coefficients (ADC), but in opposite directions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the hyperintensity in T 2 weighted images has been used to show edema, neuronal loss or, the consequence of tissue atrophy and partial volume effect. The hippocampal T 2 relaxation time has been reported to increase during the first 7 days after TBI induced by controlled cortical impact (Obenaus et al, 2007). A 3 month follow-up showed enlarged ventricles, cisterns, and that the necrotic tissue in the primary contusion site was absorbed and replaced by cerebrospinal fluid (Iwamoto et al, 1997).…”
Section: Non-invasive Imaging and Animal Models Are Needed For Undersmentioning
confidence: 99%
“…A 3 month follow-up showed enlarged ventricles, cisterns, and that the necrotic tissue in the primary contusion site was absorbed and replaced by cerebrospinal fluid (Iwamoto et al, 1997). Diffusion weighted imaging has shown decreased apparent water diffusion (ADC) acutely (<24 hours) after TBI followed by increased diffusion days or weeks after TBI (Albensi et al, 2000;Obenaus et al, 2007;Onyszchuk et al, 2007;Van Putten et al, 2005;Vink et al, 2001). Histological studies in rat models have verified these aforementioned MRI findings and the robust cellular loss and cavity formation in the primary cortical contusion site during the early weeks post-injury, the degeneration has been found to be selective for certain cell types and brain regions (Conti et al, 1998;Cortez, McIntosh, Noble 1989a;Hallam et al, 2004;Raghupathi et al, 2002;Rink et al, 1995;Sato et al, 2001) and it has been demonstrated to go on up to 1 year (Bramlett et al, 1997;Pierce et al, 1998;Smith et al, 1997).…”
Section: Non-invasive Imaging and Animal Models Are Needed For Undersmentioning
confidence: 99%